CHOLEDOCHAL CYST AND BILIARY STONE - Saeed, Anjum; Assiri, Asaad (Journal of Ayub Medical College Abbottabad, 2017)
Choledochal cyst is not an uncommonly seen entity in children. Presentation may be varied and at different age groups. Abnormal pancreaticobiliary junction is usually a phenomenon in acquired type of choledochal cyst. A four years old child presented with symptoms of acute viral hepatitis A but persistence of symptoms beyond the usual time necessitated other conditions to be considered. Choledochal cyst was the final diagnosis complicating with biliary stone which was managed by surgical excision. Choledochal cyst is not an uncommonly seen entity in children. Presentation may be varied and at different age groups. Abnormal pancreaticobiliary junction is usually a phenomenon in acquired type of choledochal cyst. A four years old child presented with symptoms of acute viral hepatitis A but persistence of symptoms beyond the usual time necessitated other conditions to be considered. Choledochal cyst was the final diagnosis complicating with biliary stone which was managed by surgical excision. Keywords: choledochal cyst; biliary stones, children